IMPLEMENTATION OF THE IJEN GEOPARK EDUCATION PROGRAM IN SCHOOLS TO SUPPORT SUSTAINABLE DEVELOPMENT - Titis Sari Hanggardimas Siwi Hartanti; Syamsul Bachri; Heni Masruroh; Tuti Mutia; Sumarmi Sumarmi (GeoEco, 2024)
Collaboration between Ijen Geopark and school has been identified as a significant driver in advancing sustainable development in Bondowoso. Research conducted aimed to explore how the integration of The Ijen Geopark education program within school contributes to sustainable development in the region. Employing a qualitative approach with a descriptive method, data collection encompassed observation, interview, and documentation. Key informants included the Ijen Geopark Manger and representative from schools. Findings from the study revealed several outcomes: 1). The implementation of the Ijen Geopark education program, which is comprised some initiatives such as:a).Geopark goes to School, b). Integration of Ijen Geopark subject material, c). Geopark Corner, d). School goes to Geopark, and e) establishment of Ijen Geopark Ambassadors.2). Challenges were identified, particularly regarding partnerships at the high school/vocational school level.3). The impact of the program was delineated, highlighting increased understanding among students regarding the interplay between humans and the environment, heightened awareness regarding the importance of nature conservation career prospects in natural sciences, environmental studies, and nature conservation.  It is hoped that this educational program will be sustainable and have an impact on schools and impactful.